Option or obligation? The determinants of labour supply preferences in Britain - René Böheim; Mark P. Taylor (University of Essex, Institute for Social and Economic Research (ISER), 2001)
We examine subjective data on desired hours of work from the BHPS and investigate which individuals are able to work their desired number of hours at the prevailing wage, which individuals are under-employed and which are over-employed. Our evidence suggests that about 40% of men and women in paid employment prefer to work a different number of hours at their current wage, and the majority of these prefer to work fewer hours. Multivariate analysis shows that differences in work time preferences depend on observed job and employer related characteristics, individual demographics, local labour demand and unobserved individual specific effects.
Keywords: 330